Elucidation of critical chemical moieties of metallo-β-lactamase inhibitors and prioritisation of target metallo-β-lactamases - Jung Hun Lee; Sang-Gyu Kim; Kyung-Min Jang; Kyoungmin Shin; Hyeonku Jin; Dae-Wi Kim; Byeong Chul Jeong; Sang Hee Lee (Taylor & Francis Group, 2024)
AbstractThe urgent demand for effective countermeasures against metallo-β-lactamases (MBLs) necessitates development of novel metallo-β-lactamase inhibitors (MBLIs). This study is dedicated to identifying critical chemical moieties within previously developed MBLIs, and critical MBLs should serve as the target in MBLI evaluations. Using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), a systematic literature analysis was conducted, and the NCBI RefSeq genome database was exploited to access the abundance profile and taxonomic distribution of MBLs and their variant types. Through the implementation of two distinct systematic approaches, we elucidated critical chemical moieties of MBLIs, providing pivotal information for rational drug design. We also prioritised MBLs and their variant types, highlighting the imperative need for comprehensive testing to ensure the potency and efficacy of the newly developed MBLIs. This approach contributes valuable information to advance the field of antimicrobial drug discovery.